Pengaruh Kompetensi terhadap Penempatan Kerja Karyawan di PT Gapura Angkasa Bandar Udara Husein Sastranegara Bandung - Fazrin, Desti Nur’amalia; Sutarwati, Sri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In work placement, the competence of each employee must be considered with the aim that the quality, quantity and timeliness of work can be maximized. Competence can help an organization in an effort to improve the quality of employees and their work placements and the company is able to develop and survive in a competitive competitive environment as well as the support of employees who are competent in their fields. This study aims to determine the effect of competence on employee placement at PT. Gapura Angkasa Husein Sastranegara Airport Bandung. This study uses a quantitative descriptive research method with data collection techniques using a questionnaire distributed to employees of PT. Gapura Angkasa Husein Sastranegara Airport Bandung and data processing with the SPSS program. Population and sample in this study HR PT. Gapura Angkasa Husein Sastranegara Airport, Bandung, with a total of 37 employees. The results of the study show that competence affects employee job placement as evidenced by the results of data processing, namely t count is greater than t table (5,862 > 2,753) with a significance value of probability, namely 0.000 <0.05, it can be said that Ha is accepted and Ho is rejected. The amount of influence obtained from the data is 49.5% and the remaining 50.5% is influenced by other factors not discussed in this study. Keywords: Competence, Employee Work Placement, PT. Gapura Angkasa, Bandung Husein Sastranegara Airport.